Bιβλιοκρισία: Charles BARBER / Stratis PAPAIOANNOU, εκδ., Michael Psellos on Literature and Art: A Byzantine Perspective on Aesthetics, [Michael Psellos in Translation], University of Notre Dame Press, Notre Dame/Indiana 2017 - LOUKAKI, Marina (Byzantina Symmeikta, 2018)
Bιβλιοκρισία: Charles BARBER / Stratis PAPAIOANNOU, εκδ., Michael Psellos on Literature and Art: A Byzantine Perspective on Aesthetics, [Michael Psellos in Translation], University of Notre Dame Press, Notre Dame/Indiana 2017